(untitled) (Heritage, 2026)
The initial knowledge that Dositej acquired in the library of the Hopovo Monastery, supported by his curiosity, led him on a fabulous journey of knowledge – into the “kingdom of ideas”, where he absorbed a variety of ideas, from the ideas of ancient and classical thought to European Enlightenment thinkers and rationalists. In his works, Dositej tells about his epistemologically motivated “wandering”, or intellectual nomadism, in the first person, which represents the authentic narrative of his philosophical, and later also Enlightenment opus. The aim of the paper is to gain a deeper insight into the intellectual nomadism of Dositej Obradović and to assess his achievements, as well as his impact on Serbian society. For the purposes of the paper, the historical-comparative, as well as the analytical-synthetic method was used, which is especially visible in the part that relates to Dositej’s travels and the knowledge he acquired in the countries in which he stayed. The conclusion of the paper is that Dositej Obradović, thanks to his intellectual nomadism, brings to his writing style a radiant spirit of reason, research and humanism, which are distinguished by clarity and rationality, as well as universalism and tolerance, and that his works transcend national themes and borders. As a sincere advocate of universal human values, he emphasizes the importance of tolerance in his writings, thus calling on readers to accept diversity and reject prejudice. His discussions lead to critical thinking, encouraging readers to question dogmas and seek new knowledge. Dositej Obradović’s intellectual nomadism transcends the usual boundaries, known languages, and disciplines of the traveling students and teachers of that time. His intellectual legacy, which endures and is meaningful to us today, is a beacon that guides us through the labyrinth of ideas, and continues to inspire future generations, reminding us that the pursuit of knowledge knows no boundaries.